2016
DOI: 10.1136/jclinpath-2016-203936
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominalCandidaspp infection in acute abdomen in a quality assurance (QA)-certified academic setting

Abstract: AimsTo evaluate the contribution of light microscopy to detecting Candida spp infection in patients with complicated intra-abdominal infections (IAIs) admitted for acute abdomen to a quality assurance (QA)-certified surgical emergency ward.MethodsWe conducted a retrospective study (2008–2012) of 809 abdominal intraoperative or biopsy tissue specimens obtained from patients admitted with acute abdomen and microbiological samples positive for Candida spp. Demographic data, mortality, comorbidities, specimen type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…In our case series, we underlined that a longer OA maintenance increases the risk of developing Candida infection. In [ 47 ], it is reported that Candida peritonitis is burdened by a high mortality rate (about 38%) and our case series attests to these values. Anyway, in our study, we must consider some biases.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our case series, we underlined that a longer OA maintenance increases the risk of developing Candida infection. In [ 47 ], it is reported that Candida peritonitis is burdened by a high mortality rate (about 38%) and our case series attests to these values. Anyway, in our study, we must consider some biases.…”
Section: Discussionsupporting
confidence: 87%
“…As revealed by Cristaudo et al [ 36 ], currently, there are no published reviews of prognostic factors with regard to definitive fascial closure, mortality, and intra-abdominal complications of patients being managed with OA. Intra-abdominal infections are considered as emergencies, and a successful outcome depends on early diagnosis, an appropriate surgical treatment, and adequate antibiotic therapy [ 47 ]. The control of invasive Candida infections is related to a reduced mortality [ 23 , 38 , 47 ]; nevertheless, criteria for starting an empirical antifungal therapy are poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is up to the "endocarditis multidisciplinary team" to understand, based on the history, local epidemiology, and clinical picture of the patient, what is the right antibiotic therapy and the timing, if necessary, of surgery [16][17]. Previously, we reported on the importance of multidisciplinary team (MDT) meetings in a Quality Assurance (QA)-certified academic setting [18].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of C. albicans and non- C. albicans species was comparable in this study, with non- C. albicans spp. being related mainly to critically ill surgical patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%